Proposta de modelo inteligente de definição de produto para atendimento à diretiva RoHS - Santos, José Altair Ribeiro dos (2015)
Manufacturing companies need to integrate their internal processes digitally to become more competitive and deliver higher quality products to the consumer market. Information defined at early design stages needs to be recovered at all stages of the life cycle of a product. To accomplish this, information models that incorporate intelligence and enable the representation of the real world are necessary. On the other hand, electronic products manufacturers need to comply with environmental requirements present in regulatory frameworks as the RoHS Directive in order to offer their products in several countries. The present work proposes the application of semantic models for helping companies meet the requirements established by the RoHS Directive. A model, created using a reference ontology, establishes semantic relationships between entities that represent product lifecycle stages, product structure and business objects. Business processes, modeled in the form of activity and information flows, are linked to RoHS requirements that can be viewed through the reports in the Essential Project open source framework. The resulting semantic model is, therefore, useful for converting environment-related needs to design requirements through a product development process that addresses the RoHS Directive. A consumer electronics product has been selected for demonstrating the feasibility of the proposed solution.